A Functional SNP in the Promoter of LBX1 Is Associated With the Development of Adolescent Idiopathic Scoliosis Through Involvement in the Myogenesis of Paraspinal Muscles - Leilei Xu (Frontiers Media S.A., 2021)
Previous studies have shown that LBX1 is associated with adolescent idiopathic scoliosis (AIS) in multiple populations. For the first time, rs1322330 located in the putative promoter region of LBX1 was found significantly associated with AIS in the Chinese population [p = 6.08 × 10–14, odds ratio (OR) = 1.42, 95% confidence interval of 1.03–1.55]. Moreover, the luciferase assay and electrophoretic mobility shift assay supported that the allele A of rs1322330 could down-regulate the expression of LBX1 in the paraspinal muscles of AIS. In addition, silencing LBX1 in the myosatellite cells resulted in significantly inhibited cell viability and myotube formation, which supported an essential role of LBX1 in muscle development of AIS. To summarize, rs1322330 may be a novel functional SNP regulating the expression of LBX1, which was involved in the etiology of AIS possibly via regulation of myogenesis in the paraspinal muscles.